Effects of high Zn and Pb concentrations on Phragmites australis (Cav.) Trin. Ex. Steudel: Photosynthetic performance and metal accumulation capacity under controlled conditions. Issue 1 (2nd January 2016) - Bernardini, A.; Salvatori, E.; Guerrini, V.; Fusaro, L.; Canepari, S.; Manes, F.
Abstract: The response of Phragmites australis (Cav.) Trin. Ex. Steudel to zinc (Zn) and lead (Pb) was studied separately in two hydroponic tests, during a three weeks experiment. The effects on ecophysiology and biomass partitioning were evaluated during the metal treatments and at the recovery, and total metal content and accumulation capacity in different plant organs were assessed. Zn and Pb had different effects on the overall measured parameters, highlighting different mechanism of action. In particular, Zn concentration was higher in roots and, being a micronutrient, it was translocated into leaves, producing a reduction of assimilation rate, stomatal conductance (–71.9 and –81.3% respect to the control plant respectively), and a strong down regulation of photosystems functionality both at PSII and PSI level. Otherwise, Pb was accumulated mainly in the more lignified tissue such as rhizomes, with slightly effect on gas exchange. Chlorophyll a fluorescence highlighted that Pb inhibits the electron transfer process at the PSI donor side, without recovery after the removal of the metal stress. Despite these physiological limitations, P. australis showed a high capacity to accumulate both metals, and only slight reduction of biomass, being therefore a suitable species for phytoremediation interventions.